2015
DOI: 10.1089/jmf.2014.3371
|View full text |Cite
|
Sign up to set email alerts
|

Houttuynia cordataExtract Improves Physical Endurance Performance by Regulating Endothelial Production of Nitric Oxide

Abstract: Vascular function is mediated by various regulatory molecules, including endothelial nitric oxide (NO), which regulates the vasodilation of smooth muscle cells. We investigated whether standardized Houttuynia cordata extract (SHCE) could improve physical endurance performance by regulating the endothelial production of NO. For the standardization of Houttuynia cordata (HC) extract, its bioactive components were identified and quantified using ultraperformance liquid chromatography-mass spectrometry. Bioaccessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In a study, Yang et al showed the antioxidative properties of 50% methanolic extract of HC against palmitateinduced oxidative stress in human aortic endothelial cells. The authors showed that HC extract increased NO production through insulinmediated eNOS phosphorylation in human aortic endothelial cells (Yang et al, 2015).…”
Section: Role Of H Cordata In Oxidative Stress-related Molecular Mecmentioning
confidence: 99%
“…In a study, Yang et al showed the antioxidative properties of 50% methanolic extract of HC against palmitateinduced oxidative stress in human aortic endothelial cells. The authors showed that HC extract increased NO production through insulinmediated eNOS phosphorylation in human aortic endothelial cells (Yang et al, 2015).…”
Section: Role Of H Cordata In Oxidative Stress-related Molecular Mecmentioning
confidence: 99%
“…In order to examine the amounts of bioactive components accessible to the gastrointestinal (GI) tract, the method by Yang et al and Son et al was used with a slight modification [34,35]. The GI tract was composed of three-stages of an in vitro human digestion model system, which were salivary, stomach, and upper intestine steps.…”
Section: Methodsmentioning
confidence: 99%
“…Houttuynia cordata Thunb (H.cordata), is a perennial native medicinal plant widely used in folk medicine in Japan, Korea, China and Southeast Asia [1]. Traditionally, H.cordata was used as a folk medicine for diuresis, anti-viral [2], anti-oxidant [3][4][5], anti-bacterial [6], anti-inflammatory [7][8][9], and anti-obesity [10,11]. In 2014, Hyun Kang reported that H.cordata extract (HCE) significantly attenuated lipid accumulation in human HepG2 hepatocytes, and the hypolipidemic effects of HCE were induced by activating AMPK signaling which then inhibits lipid biosynthesis [12].…”
Section: Introductionmentioning
confidence: 99%